Stephen Massey: a career in visual neuroscience - Mills, Stephen L.; Marshak, David W. (Frontiers in Ophthalmology, 2023)
This review is both an introduction to the virtual festschrift for Stephen C. Massey and a memoir by his longtime collaborator, Stephen L. Mills. The references cited here are only a few of the highlights of Dr. Massey’s career.